“El mensaje radial del obispo de la diócesis de Riobamba “el Pozo de Sicar”, en la formación de conciencia social, del grupo de la Pastoral juvenil Diocesano, de junio a diciembre del 2014”. - Rosero López, Luis Alberto (2017)
This work entitled “The radial message of the Bishop of the Diocese of Riobamba - El Pozo de Sicar," in the foundation of Social Consciousness into the group of Diocesan Youth Ministry, from June to December 2014, "The radial message of the Bishop of the Diocese of Riobamba". The variables were based on the structure of the radio messages according the type of arguments used in each one of the programs with the aim of persuading listeners, this research has allowed us to know how based on the message allows the structure the conscience in the citizens; for the research, the study group had 36 members of "The Youth Ministry of the Diocese of Riobamba", the method used was deductive and inductive as technique , the survey and the questionnaire instrament supported the improvement of the general and Specific objectives